THE PRESENCE OF AFRICANS IN THE DUTCH EAST INDIES IN THE 19TH CENTURY: A HISTORICAL REVIEW - Anita; Ansgarius Nggera (SOSIOEDUKASI, 2026)
This study aims to analyze the presence of Africans in the Dutch East Indies in the 19th century as a historical review. This study uses a qualitative research method with a historical approach, through a literature study of books, archives, and scientific journals relevant to the history of Africans in the Dutch East Indies. The purpose of this study is to determine the background of the recruitment of Africans in the Dutch East Indies, the formation and characteristics of Zwarte Hollander, distribution and placement in the Dutch East Indies, and to determine the role of Africans in colonial military operations. The results of the study indicate that the recruitment of Africans in the Dutch East Indies did not occur spontaneously and through several reasons, including the Dutch experiencing a serious crisis in the supply of military personnel in the Dutch East Indies, so the Dutch recruited African soldiers to join the KNIL.